ANALISIS FAKTOR-FAKTOR PERTIMBANGAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK HUNIAN DI KECAMATAN TEMBALANG KOTA SEMARANG - Edy Suryawardana; Tri Endang Yani (Jurnal Dinamika Sosial Budaya, 2017)
Semarang city population growth is very fast. The surge in the population growth rate is one of the factors increasing demand for housing. The objective of this study was to determine whether the price factor can influence consumer decisions significantly in choosing housing, to determine whether the location factors can influence consumer decisions significantly in choosing housing, to determine whether the factor of residential facilities may affect consumer decisions significantly in choosing housing as well as to determine whether the home design factors may affect consumer decisions significantly in choosing housing.Research conducted at the District Tembalang housing in the city, with the respondents, 60 consumer products Tembalang housing in the District of Semarang. The method of data collection / dissemination of the questionnaire using cluster sampling. While the analysis of the data in this study using SPSS 22. Rel, tailored to each hypothesis, having previously performed testing of the quality of the data and the classical assumption.Price affect positively and significantly on purchasing decisions, the location affect positively and significantly related to the purchase decision, the facility affect positively and significantly related to the purchase decision, design product has positive and significant influence on purchasing decisions.